De impact van de coronacrisis op het subjectief welbevinden van (internationale) studenten in Nederland - Mol, Christof Van; Dekkers, Sabien; Verbakel, Ellen (Mens & Maatschappij, 2021)
Angaben zum Inhalt: „The impact of the COVID-19 pandemic on subjective well-being of (international) higher education students in the Netherlands In this paper we investigate the impact of the COVID-19 pandemic on subjective well-being of higher education students in the Netherlands. More specifically, we compare international students and Dutch students, based on the Dutch data of the COVID-19 International Student Well-Being Study, a cross-sectional survey conducted between May-July 2020 among higher education students across the Netherlands (N = 10.491). Based on the sociological literature on the relationship between social capital and subjective well-being, we investigate in particular whether changes in social contact during the first lockdown can explain differences in subjective well-being between international and Dutch students. Our results suggest that although international students report lower levels of subjective well-being compared to Dutch students, these differences cannot be directly explained by (changes) in social contact during the lockdown.“
Keywords: Lebensqualität; Student; Studentin; Universität; Zufriedenheit

The impact of the COVID-19 pandemic first lockdown period on the work and well-being of academics in the Netherlands - Bol, Thijs; Derks, Belle; Poorthuis, Lidwien (De Jonge Akademie; Het Landelijk Netwerk Vrouwelijke Hoogleraren, 2021)
Keywords: Arbeitsbedingungen; Universität

De post-coronatuin van Akademos zal digitaal en open zijn. Hoe de coronapandemie wetenschap en universiteiten voorgoed verandert - Burgelman, Jean-Claude (Post viraal naar een nieuw normaal. VUB-stemmen over de impact van corona op onze samenleving, 2020)
Keywords: Digitalisierung; Open Science; Universität; Wissenschaft